Perlindungan Hukum Terhadap Korban dalam Kasus Penganiayaan yang Mengakibatkan Luka Berat: Studi Putusan No. 372/Pid.B/2019/PN Srh - Mega Sartika; Dani Sintara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Serious abuse is a criminal act that results in serious injury to the victim and is considered a serious crime in various jurisdictions. This research examines legal protection for victims of serious abuse and the application of criminal sanctions in the Indonesian legal context with a focus on Case Number 372/Pid.B/2019/PN Srh. This case involves the defendant Diantoro Saragih Alias ​​Dian, who was proven guilty of committing assault which resulted in serious injuries. This study evaluates three main aspects: 1. factors that cause cases of abuse that result in serious injuries? 2. What is the legal protection for victims in cases of abuse that results in serious injury case 372/Pid.B/2019/PN Srh? 3. How are criminal sanctions applied for perpetrators of cases of abuse that result in serious injury based on case 372/Pid.B/2019/PN Srh? assess the effectiveness of law enforcement in providing justice for victims, as well as upholding social order. It is hoped that the results of this study will provide insight into the application of the law in cases of serious abuse, as well as increase the effectiveness of the legal and judicial protection system in Indonesia. optimized, strengthen the justice system, and improve justice and security in society.